Oud neg.nr. 66842-66877. 'Congres ABC, discussie'. Portretten en een notitie van de namen van desbetreffende deelnemers 1-36 - Haas, Joh. de
Oud neg.nr. 66842-66877. 'Congres ABC, discussie'. Portretten en een notitie van de namen van desbetreffende deelnemers 1-36.